Communicative teaching methods in technical education: integrative approach - Lemeshchenko-Lagoda, Viktoriia; Лемещенко-Лагода, Вікторія Володимирівна; Лемещенко-Лагода, Виктория Владимировна; Movchan, Serhii; Мовчан, Сергій Іванович; Мовчан, Сергей Иванович (Мелітопольський фаховий коледж ТДАТУ, 2021)
Based on the active usage of developed engineering solutions for studying the field of "Architecture and Construction", in order to consider the theoretical material in-depth, it is proposed to use the CLIL method, tested by the authors while teaching other related disciplines. The use of the CLIL methodology, which extends the communication conditions for the use and study of a foreign language, involves the presentation of some key issues in a foreign language, and the use of the same test questions in compiling a training package.
Keywords: optical-mechanical systems; laser; laser emitter; ommunication conditions; CLIL